Liquid metal infiltration of silicon based alloys into porous carbonaceous materials Part-III: Experimental verification of conversion products and infiltration depth by infiltration of Si-Zr alloy into mixed SiC/graphite preforms. Issue 1 (January 2023) - Naikade, Manoj; Hain, Caroline; Kastelik, Kaja; Parrilli, Annapaola; Graule, Thomas; Weber, Ludger; Ortona, Alberto
Abstract: Porous carbonaceous preforms, made from graphite and silicon carbide (SiC) powders, with varying graphite powder mass fractions and particle sizes, were infiltrated at 1500 °C and 1700 °C by Si-8 at. pct Zr alloy to produce dense Si-Zr-SiC composites. The experiments were performed in a graphite chamber vacuum furnace at 10 − 2 mbar. The most desirable results were obtained for preforms composed of a mixture of graphite and SiC powders, with preforms containing 15–20 % mass fraction of graphite and infiltrated at 1500 °C. The banding of the Zr-rich phase observed in the cross-sections of SiC-C pre- forms infiltrated by the Si-Zr alloy may help in decoding the reactive infiltration process with binary alloys.